Characteristics of Gas–Liquid Slug Flow in Honeycomb Microchannel Reactor - Youkai Jiang; Yaheng Zhang; Jie Zhang; Zhiyong Tang (Energies, 2022)
The gas–liquid slug flow characteristics in a novel honeycomb microchannel reactor were investigated numerically and experimentally. Computational fluid dynamics (CFD) modeling was carried out with Comsol finite element software using the phase-field method, and the simulation results were verified by micro-particle image velocimetry (micro-PIV) analysis. The breakups of liquid slugs at the bifurcations of current honeycomb microchannel followed a complex behavior, leading to non-uniformity in each branch. The pressure distribution inside the microreactor was closely related to the phase distribution. The increasing inlet gas velocity increased the gas phase volume fraction, as well as the gas slug length. Higher gas velocity resulted in stronger turbulence of the liquid phase flow field and a deviation of residence time distribution from normal distribution, but it was favorable to even more residence time during the liquid phase. There also exists a secondary flow in the gas–liquid interface. This work reveals the intrinsic intensified effect of honeycomb microchannel, and it provides guidance on future microreactor design for chemical energy conversion.